Academic Senate Minutes 2003-04-24 - Academic Senate:::::::::
Report from Chair. Correspondence received from Kerry Mazzoni. Agenda amended and approved. Approval of full minutes delayed, summary of actions submitted. Reports from President, (Rose Bruce for) Provost, Vice-President of Administration and Finance. Two information items offered – Resolution on Large Enrollment Classes and Resolution from Associated Students: On Faculty Deadline for Textbook Orders. First reading on Resolution on University Community Solidarity Fund. Report from Stuart Jones, Director of Development.